Analysis of hepatic steatosis control in patients after bariatric surgery (Research, Society and Development, 2021)
Purpose: To evaluate the association between the control of hepatic steatosis (HS) and the postoperative period of bariatric surgery in a private institution in Sergipe. Methodology: Retrospective observational and single-center study, with data collected through an online form, previously authorized by 57 patients, regardless of gender, with Class III or Class II obesity associated with comorbidities, who underwent bariatric surgery using the techniques of Vertical Gastrectomy (Gastric Sleeve) and Roux-en-Y Reduction Gastroplasty (Gastric Bypass) by videolaparoscopy, in a private institution in Aracaju/SE, between 2019 and 2021. After applying the exclusion criteria, 45 patients were analyzed. Data were analyzed using percentage frequency, Pearson and McNemar tests. It was adopted a significance level of 5%. Results: In the preoperative period, it was found a 66.7% prevalence of HS and in the postoperative period the prevalence was found to be 16.7%, with a reduction in the degree of the pathology to HS class I, verified through ultrasonographic examination. There was an 83.3% success rate in the patients with HS in the preoperative period. Of the 83.3%, there was a clinical improvement in 23 (67.6%) of those who underwent Gastric Sleeve surgery, as well as an improvement of 7 (63.6%) who underwent Gastric Bypass surgery. Conclusion: There was a significant association between bariatric surgery and the resolution of hepatic steatosis, regardless of the surgical technique used.